2014
DOI: 10.1111/gec3.12131
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Next Generation Farmers: A Conceptual Framework to Bring the Potential Successor into Focus

Abstract: Intergenerational succession is understood as an integral facet of the family farm. The importance of the succession process and more specifically, successor identification, are critically discussed in the context of the widely propagated projections of global population growth and associated demands on the agricultural sector. Having established the merits of successor identification, the article then highlights the absence of the ‘potential successor’ from contemporary research and continues by offering a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 21 publications
0
42
0
2
Order By: Relevance
“…Interviews typically took place in farmers' and potential successors' homes, but a small number were conducted at a neutral location (a café) at the behest of the participant. Potential successors were defined as someone who could potentially gain managerial control of the farm, including someone assumed to be the future successor by virtue of his or her relationship to the farmer and those actively moving toward gaining managerial control of the farm (Chiswell ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interviews typically took place in farmers' and potential successors' homes, but a small number were conducted at a neutral location (a café) at the behest of the participant. Potential successors were defined as someone who could potentially gain managerial control of the farm, including someone assumed to be the future successor by virtue of his or her relationship to the farmer and those actively moving toward gaining managerial control of the farm (Chiswell ).…”
Section: Methodsmentioning
confidence: 99%
“…In light of the long‐standing cultural expectation that the eldest son would become the successor (de Hann ; Gasson and Errington ; Kuehne ; Silvasti ), as well as the scarcity of engagement with the potential successor in previous research (Chiswell ), we tried to interview farmers and their potential successors separately . We hoped that separate interviews would allow both parties to talk openly and honestly about their hopes, motivations, and plans for the farm, without fear of repercussions, in a way that they might not have been able to do in a joint interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These opportunities need to be acknowledged by policymakers. Moreover, for any policy to be successful, engagement is needed with the potential next generation of farmers (Chiswell, 2014). For instance, in order to facilitate children to take over their parent's farm without immediately incurring debts, inheritance taxes could be reduced (van der Veen et al, 2002).…”
Section: Strategies To Support Family Farmersmentioning
confidence: 99%
“…While it has been suggested that the number of willing successors may be declining, recent analyses have suggested that succession remains a central aspect of farming in UK, as elsewhere (see Riley , Chiswell ).…”
mentioning
confidence: 99%